2020
DOI: 10.1111/eos.12746
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HPV detection rate in formalin‐fixed paraffin‐embedded tissues of head and neck carcinoma using two DNA extraction kits and three amplification methods

Abstract: zevi c A. Comparison of HPV detection rate in formalin-fixed paraffin-embedded tissues of head and neck carcinoma using two DNA extraction kits and three amplification methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…The use of high temperatures during extraction, however, has been suggested to interfere with multiplex qPCR performance [26], while lower de-cross-linking temperatures have been shown to be beneficial in the assessment of somatic variants in cancer patients [27]. The two protocols used in this study have been previously evaluated by Bozic et al [12] who found comparable detection rates of human papillomavirus in FFPE samples, albeit higher yields of total DNA were obtained with the FFPE kit. This was also the case in our study, where we determined higher ratios of the human single-copy gene RNase P and of viral findings in the samples extracted with the FFPE kit, although the difference to the standard protocol was not significant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of high temperatures during extraction, however, has been suggested to interfere with multiplex qPCR performance [26], while lower de-cross-linking temperatures have been shown to be beneficial in the assessment of somatic variants in cancer patients [27]. The two protocols used in this study have been previously evaluated by Bozic et al [12] who found comparable detection rates of human papillomavirus in FFPE samples, albeit higher yields of total DNA were obtained with the FFPE kit. This was also the case in our study, where we determined higher ratios of the human single-copy gene RNase P and of viral findings in the samples extracted with the FFPE kit, although the difference to the standard protocol was not significant.…”
Section: Discussionmentioning
confidence: 98%
“…Most importantly, the analytical sensitivity of detection of low-copy viral nucleic acids in archival and/or highly degraded samples has not been assessed. Indeed, most of the existing reports on FFPE tissue specimens have been PCR-based and focused on oncogenic viruses in tumor samples, in which the viral copies are commonly very high [10][11][12][13][14]. For example, in cervical cancer, human papillomaviruses can have average copies of 10 7 /µg in contrast to 10 2 /µg of most persistent viruses in healthy tissues [15].…”
Section: Introductionmentioning
confidence: 99%
“…During infection, viral DNA sequences of HPV are incorporated into cellular DNA and play a key role in the promotion of neoplasm growth and malignant transformation of SNIP [ 32 ]. The detection method and detection rate of HPV-PCR are important points, and there have been several studies that employ HPV-PCR in FFPE samples [ 33 , 34 , 35 ]. The internal control gene amplification was performed to assess the validity of the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the PGMY/GP+ nested PCR is the most appropriate primer set for the detection of HPV DNA using FFPE samples from OSCC. In turn, Božić et al [ 45 ] have compared HPV detection rate in FFPE of head and neck carcinoma using three amplification methods: single PCR and real-time PCR and nested PCR. In their study there was not HPV amplification in any of the 50 FFPE samples using the single PCR and real‐time PCR, whereas HPV DNA was detected in 22% of samples using nested PCR.…”
Section: Discussionmentioning
confidence: 99%